2021
DOI: 10.1029/2020wr028090
|View full text |Cite
|
Sign up to set email alerts
|

Influences on Discharge Partitioning on a Large River Delta: Case Study of the Mississippi‐Atchafalaya Diversion, 1926–1950

Abstract:  Minor erosion measured in the Mississippi River would have reduced Atchafalaya Discharge, had Atchafalaya Basin remained constant. Lacustrine Deltas in the Atchafalaya Basin did not change partitioning, as they were downstream of a reach with steep water surface slope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 65 publications
4
14
1
Order By: Relevance
“…Shaw et al. (2021) also showed that the dredging of new connecting channels for navigation in the channel network of the lower Atchafalaya River leads to a decreasing water surface slope in the dominant channel, which is consistent with our results (Figure 8). Interestingly, according to Konkol et al.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Shaw et al. (2021) also showed that the dredging of new connecting channels for navigation in the channel network of the lower Atchafalaya River leads to a decreasing water surface slope in the dominant channel, which is consistent with our results (Figure 8). Interestingly, according to Konkol et al.…”
Section: Discussionsupporting
confidence: 92%
“…The asymmetry of water partitioning at the delta apex decreases with increasing river discharge (Huang et al, 2022), which is consistent with our findings (Figure 4). Shaw et al (2021) also showed that the dredging of new connecting channels for navigation in the channel network of the lower Atchafalaya River leads to a decreasing water surface slope in the dominant channel, which is consistent with our results (Figure 8). Interestingly, according to Konkol et al (2022), deltaic channel networks are also similar to systems such as leaf vascular networks, where the numerous secondary connecting veins link main veins and thus create loops in the network to improve the resilience of the network to perturbations such as vein damage and variations in flow (Katifori et al, 2010).…”
Section: Mechanism Of Connecting Channel On Flow Adjustmentsupporting
confidence: 92%
See 1 more Smart Citation
“…At present, shorelines of many deltas in the world are experiencing land loss due to declining sediment supply and accelerating rates of sea‐level rise (Blum & Roberts, 2009; Syvitski & Saito, 2007). Because large river deltas are densely populated and are transportation hubs and industrial and commercial centers, artificial bifurcation have been implemented, or are being considered, as a viable engineering tool to divert flow and sediment for combating coastal land loss, especially on those densely populated deltas such as the Yellow River delta (Carlson et al, 2021; Syvitski & Saito, 2007) and the Mississippi River Delta (Shaw et al, 2021; Wang & Xu, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Because large river deltas are densely populated and are transportation hubs and industrial and commercial centers, artificial bifurcation have been implemented, or are being considered, as a viable engineering tool to divert flow and sediment for combating coastal land loss, especially on those densely populated deltas such as the Yellow River delta (Carlson et al, 2021;Syvitski & Saito, 2007) and the Mississippi River Delta (Shaw et al, 2021;.…”
mentioning
confidence: 99%